A Deliberative Orientation to Governing Carbon Dioxide Removal: Actionable Recommendations for National-Level Action - Borth, Amanda C.; Nicholson, Simon (Frontiers in Climate, 2021)
Effective and legitimate governance of carbon dioxide removal (CDR) requires that the needs, interests, and perspectives of those liable to bear the burdens of CDR’s effects be present in decision-making and oversight processes. This ideal has been widely recognized in prior academic work. How, though, in a practical sense, is this deliberative aspect of CDR governance to be understood? In this policy brief, we look at the future incorporation of carbon removal pledges into the nationally determined contributions (NDCs) of countries under the Paris Agreement, and we argue for and explore a deliberative orientation when it comes to the inclusion of CDR into country-level climate change response goals. The aim is to provide practical guidance on deliberation as a toolkit and set of practices.